THE USE OF CONCORDANCE AND CORPORA IN TEACHING ENGLISH LANGUAGE SKILLS - Rakhimova Indira Kudrat Kizi (Journals Park Publishing, 2022)
The use of a concordance by the language learner to investigate vocabulary and structure in the target language is unfortunately in its infancy. Some research has attempted to promote this idea, but the potential benefit of concordances and hands-on learning still requires exploration. Although several studies have been conducted in order to determine the effectiveness of corpora on foreign language learning, most of these studies investigated the utility of concordances to practice one specific skill.
Keywords: concordance lines, awareness-raising, writing, grammar, vocabulary acquisition, learner-friendly, high frequency, technical, academic.